Lack of effect of atenolol on the pharmacokinetics of theophylline. - Cerasa, L A (1988)
The effects of 3 days of pretreatment with cardioselective doses of atenolol on theophylline pharmacokinetics were determined. Nine healthy nonsmoking male volunteers received 6 mg kg-1 i.v. aminophylline under baseline conditions and after both 50 mg day-1 and 100 mg day-1 atenolol. Theophylline clearance, volume of distribution and half-life were not influenced by atenolol pretreatment. These data indicate that cardioselective doses of atenolol do not alter the pharmacokinetics of theophylline.